A single chemosensor for bimetal Cu(ii) and Zn(ii) in aqueous medium. Issue 40 (6th April 2016) - Liao, Zhuang; Wang, Dan; Zheng, Jian-Quan; Tan, Hong-Wei; Zheng, Xiang-Jun; Jin, Lin-Pei
Abstract : A new quinazoline-based bimetal chemosensor for Cu(ii ) and Zn(ii ) in aqueous medium was synthesized. It can act as a "turn-off" sensor for Cu(ii ) with the excitation wavelength of 356 nm, and a "turn-on" sensor for Zn(ii ) when excited at 416 nm. Abstract : A new quinazoline derivative 6-(4-diethylamino)phenol-2-yl-(5, 6-dihydrobenzimidazo[1, 2- c ])-quinazoline (HL) and the two metal Schiff-base complexes [CuL 1 Cl]·CH3 OH (1 ) and [ZnL 1 (Ac)]·0.5CH3 CH(OH)CH3 (2 ) (HL 1 = 4-{[2-(1 H -benzoimidazol-2-yl)-phenyl imino]-methyl}-benzene-1-diethylamino-3-ol) were synthesized and characterized by single-crystal X-ray diffraction. HL is highly selective and sensitive to Cu(ii ) and Zn(ii ) ions in aqueous medium with a detection limit of 2.13 × 10 −6 and 7.19 × 10 −7 M for Cu 2+ and Zn 2+, respectively. HL can act as a "turn-off" sensor for Cu(ii ) with the excitation wavelength of 356 nm and a "turn-on" sensor for Zn(ii ) when excited at 416 nm. The Job plots, fluorescence and UV-vis titrations, 1 H NMR as well as ESI data show that the binding stoichiometry of Cu(ii )/Zn(ii ) with HL is 1 : 1. The binding sites of HL with Cu(ii )/Zn(ii ) are two nitrogen atoms and one oxygen atom, forming Cu(ii )–L 1 and Zn(ii )–L 1 complexes. This agrees with the crystal structures of1 and2 .